PENGARUH POLA ASUH ORANG TUA DALAM MENINGKATAN PRESTASI BELAJAR ANAK - Rizky Anggalia Kusuma; Henry Aditia Rigianti (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
This study aims to describe parenting styles applied by parents to children, to describe children's learning achievements, and to find out differences in learning achievement based on parenting styles. By understanding existing developments, it is hoped that parents as first and foremost teachers for children can improve parenting according to development, and see children's abilities in terms of learning. The research method in this scientific work uses the ex post facto research method. With an understanding that this research is conducted by examining an event that has occurred and then reviewing the factors that gave rise to the incident. Based on research through literature studies, it shows that children's learning achievement using democratic parenting is the most appropriate and very dominant so that there is an increase in learning according to their abilities, it can be concluded that appropriate parenting according to developments in this era of disruption is not something that hinders improving children's learning, but must be an opportunity to continue to guide and motivate children to learn to take advantage of the situation, and cultivate it according to the knowledge and knowledge they learn, because there are differences in children's learning achievement based on parenting styles that look like (authoritarian parenting, democratic parenting and permissive parenting). misif, very influential and expected achievements will be answered according to learning objectives. Keywords: Parenting Pattern, Learning Achievement